A comprehensive look into the volatile exometabolome of enteroxic and non-enterotoxic Staphylococcus aureus strains - Baptista, Inês (2019)
Staphylococcal food poisoning is a disease that originates significant health and economic losses and is caused by Staphylococcus aureus strains able to produce enterotoxins. The aim of this work is to go further on the study of the volatile exometabolome of S. aureus using an advanced gas chromatographic technique. Enterotoxic and non-enterotoxic strains were assessed. The volatile exometabolome profile comprised 240 volatiles belonging to ten chemical families. This volatiles were mainly by-products of branched-chain amino acids and methionine degradation, pyruvate metabolism, diacetyl pathway, oxidative stress and carotenoid cleavage. Metabolites released by the first two pathways were produced in higher contents by the enterotoxic strains. This study add further insights to S. aureus volatile exometabolome, and also shows that by applying it, it is possible to distinguish strains of S. aureus by the number of produced enterotoxins, which is especially important from the food safety point of view.